Programas de aceleração corporativa como estratégia de inovação aberta: expectativas e realidades na percepção de gestores e empreendedores - Raquel de Almeida Menezes (2020)
Among the various forms of relationship between large corporations (GCs) and startups, there is the advent of the so-called Corporate Acceleration Programs (PACs). In these, a host GC opens up to cohorts of startups as part of its open innovation strategy. The present study makes use of the theoretical paradigm of Strategy as a Process to verify, in the perception of those involved, how the strategic intention for a PAC becomes realization, and, especially, to elucidate the reasons why the objectives of a PAC may not be realized, given the differences between GCs and startups. In order to achieve this objective, for each of four important Brazilian PACs, the following players were interviewed: Institutions (GC strategists responsible for designing the interaction model with startups via PAC); Executors (middle management responsible for conducting the program) and Participants (members of startups participating in the PAC). The analysis of the collected data was performed through modeling of Cognitive Causal Maps (MCC) — i.e. MCCs were built that allowed cross-sectional analyzes between the managerial and entrepreneurial cognitions represented in the different programs. New ways of analyzing these maps have also been proposed as a methodological contribution. As a theoretical contribution, this work proposes, based on the evidence obtained, that confronting strategic intentions with actions that support them, a new strategic manifestation emerges — actions called “saboteurs”, capable of culminating in sabotaged strategies that can become unrealized, when destroyed by actions diametrically opposed to the strategy originally intended. Thus, in the search for the main causes that lead to unrealized strategy, the need to expand the model to understand the sabotaging actions emerged. Finally, the present research contributes with the description of four PACs from a multilevel view (i.e. founders, executors and participants), revealing what were the antecedents for the design of PACs, what are their main characteristics, what are the intentions of GCs and participants in relation to programs and what were their perceptions throughout the program.